Tactical features of the scene inspection in the investigation of the taking of a government official or law enforcement officer as a hostage - O. Yu. Prokopenko (Bulletin of Kharkiv National University of Internal Affairs)
The criminal offence of taking a government official or a law enforcement officer hostage under Article 349 of the Criminal Code of Ukraine is becoming increasingly relevant in today’s realities. However, in the course of the study of scientific findings, the absence of methodological recommendations for investigating this crime has been established, which negatively affects the state of combating crime. In particular, the investigation methodology includes recommendations on the specifics of certain investigative (detective) actions, the primary of which is the inspection of the scene. Thus, there is a need to conduct research on the above issue.